Utilizing differences in bTH tolerance between the parents of two-line hybrid rice to improve the purity of hybrid rice seed - Zhang, Xiuli; Wang, Qing; Fan, Guojian; Tang, Li; Shao, Ye; Mao, Bigang; Lv, Qiming; Zhao, Bingran (Frontiers in Plant Science, 2023)
Two-line hybrid rice based on Photoperiod/thermo-sensitive genic male sterile (P/TGMS) lines has been developed and applied widely in agriculture due to the freedom in making hybrid combinations, less difficulty in breeding sterile lines, and simpler procedures for breeding and producing hybrid seed. However, there are certain risks associated with hybrid seed production; if the temperature during the P/TGMS fertility-sensitive period is lower than the critical temperature, seed production will fail due to self-pollination. In a previous study, we found that the issue of insufficient purity of two-line hybrid rice seed could be initially addressed by using the difference in tolerance to βtriketone herbicides (bTHs) between the female parent and the hybrid seeds. In this study, we further investigated the types of applicable herbicides, application methods, application time, and the effects on physiological and biochemical indexes and yield in rice. The results showed that this method could be used for hybrid purification by soaking seeds and spraying plants with the bTH benzobicylon (BBC) at safe concentrations in the range of 37.5-112.5 mg/L, and the seeds could be soaked in BBC at a treatment rate of 75.0 mg/L for 36-55 h without significant negative effects. The safe concentration for spraying in the field is 50.0-400.0 mg/L BBC at the three-leaf stage. Unlike BBC, Mesotrione (MST) can only be sprayed to achieve hybrid purification at concentrations between 10.0 and 70.0 mg/L without affecting yield. The three methods of hybrid seed purification can reach 100% efficiency without compromising the nutritional growth and yield of hybrid rice.Moreover, transcriptome sequencing revealed that 299 up-regulated significant differentially expressed genes (DEGs) in the resistant material (Huazhan) poisoned by BBC, were mainly enriched in phenylalanine metabolism and phenylpropanoid biosynthesis pathway, it may eliminate the toxic effects of herbicides through this way. In summary, our study establishes a foundation for the application of the bTH seed purification strategy and the three methods provide an effective mechanism for improving the purity of two-line hybrid rice seeds.